Paleomagnetism of Khatyrka and Maynitsky superterranes, Koryak highlands, far eastern Russia (Dataset) ... - Didenko, Alexi; Harbert, William; Stavsky, Anatoly (Magnetics Information Consortium (MagIC), 2006)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Paleomagnetism of Khatyrka and Maynitsky superterranes, Koryak highlands, far eastern Russia ...